Natural red colorant via solid-state fermentation of oil palm frond by Monascus purpureus FTC 5356: effect of operating factors - Farhan, Mohd Said; Nor Farhana, Hamid (Taylor's University, 2019)
Nowadays, natural colorants are valuable in many industries as an alternative to potentially harmful synthetic colorants. Synthetic colorants may cause serious side effects such as cancer and allergies to the human. The aim of the study is to identify the effects of operating factors on the red pigment produced by Monascus purpureus FTC5356 fermented on the treated agro-biomass. The agro-biomass used is oil palm frond (OPF). The study was conducted under the solid-state fermentation using one-factor-at-a-time (OFAT) approach. Five operational factors such as the initial moisture content of OPF (% IMC) (w/w), initial pH, supplementation of nitrogen source (w/w), the percentage of petiole to leaflet and inoculums size (spores/ml) were investigated. The highest production of red pigment was reached at day 8 (2.68 AU/g dry matter). The optimal red pigment production with the treated OPF substrate was achieved at the following operational factor values: 50% (w/w) IMC, pH 6 (3.68 AU/g dry matter), 2% (w/w) peptone, 100% (w/w) petiole, and inoculums size of 10^8 spores/ml. The environmental and nutritional conditions of the substrate have proven to play a significant role in producing the red pigment.